Digital Relationality, Rights, Resilience: Conceptualising a Digital Social Ecology for Children's Birth Family Relationships When in Care or Adopted. (29th July 2022) - MacDonald, Mandi; Wright, Amy Conley; Taylor-Beswick, Amanda; Gillespie, Kathryn; Collings, Susan
Abstract: The use of digital communication technology by children residing in out-of-home care or adopted from foster care has mainly been approached hesitantly and from a risk paradigm. The Covid-19 pandemic catalysed many digital and social work intersections, including practices used for birth family contact where in-person visits were supplemented or replaced with 'virtual' contact via digital devices. Whilst technology-mediated contact is characterised as 'virtual', the relationships it facilitates and emotions it generates are very real within children's social ecology. Digital ubiquity in social life and the rapid pace of technological change presents significant ethical and practical tensions. To help social workers navigate this complexity of 'contact-in-reality' and facilitate safe, ethical use of digital communication technology for birth family contact, we connect an understanding of the dynamics of birth family contact with literature on children's use of digital technology and ecological concepts of person-in-environment to offer a digital social ecology heuristic for social work practice. Three key aspects cut across all systems and levels, referred to here as the three Digital R's: digital relationality; digital rights; and digital resilience. Future research is needed to understand how these dynamics play out. Abstract : Conversations about use of social media, mobile Internet and other digital communication technology by children in care or adopted from care often focus on risk. The Covid-19 pandemic meant that social workers had to rethink digital technology and consider how it might be used for birth family contact. When contact happens using technology, it is often thought of as 'virtual', however, these relationships and emotions are very real for children. Technological progress is happening quickly, and digital technology is everywhere. Social workers must think about how this will affect their practice. We bring together work on birth family contact, children's digital technology use and theoretical literature on the influence of environments on individuals. We offer a way of looking at these issues to help social workers consider how to use digital communication technology for birth family contact in safe and ethical ways. We propose consideration of the three Digital R's: digital relationality (digital technology and relationships); digital rights (legal protection of children's safety and opportunities whilst using digital technology); and digital resilience (digital skills and ability to cope with negative experiences). Future research is needed to strengthen empirical evidence on how these factors manifest and interact.